Clinical Outcomes of Escherichia coli Acute Bacterial Prostatitis: A Comparative Study of Oral Sequential Therapy with β-Lactam Versus Quinolone Antibiotics - Laura Gisbert; Beatriz Dietl; Mariona Xercavins; Aina Mateu; María López; Ana Martínez-Urrea; Lucía Boix-Palop; Esther Calbo (Antibiotics, 2025)
Background/Objectives: Optimal management of acute bacterial prostatitis (ABP) remains uncertain, but the use of antibiotics with good prostatic tissue penetration is critical to prevent recurrence and chronic progression. This study aimed to describe clinical characteristics and outcomes of ABP due to Escherichia coli (ABP-E.coli), compare effectiveness of sequential high-dose cefuroxime (ABP-CXM) versus ciprofloxacin (ABP-CIP), and identify risk factors for clinical failure. Methods: We conducted a retrospective study including men >18 years diagnosed with ABP-E. coli between January 2010 and November 2023 at a 400-bed hospital. Patients received oral cefuroxime (500 mg/8 h) or oral ciprofloxacin (500 mg/12 h). Outcomes over 90 days included clinical cure, recurrence and reinfection. Definitions: Clinical cure—resolution of symptoms without recurrences; recurrence—new ABP episode with the same E. coli strain; reinfection—ABP involving different microorganism or E. coli strain; clinical failure—lack of cure, recurrence, or reinfection. Results: Among 326 episodes (158 ABP-CXM, 168 ABP-CIP), ABP-CXM patients were younger (median 63.5 vs. 67.5 years, p = 0.005) and had fewer comorbidities. Clinical cure was higher in ABP-CIP (96.9% vs. 85.7%, p < 0.001). Recurrence occurred only in ABP-CXM (6.96% vs. 0%, p < 0.001), while reinfection and mortality were similar. Multivariable analysis showed ciprofloxacin was protective against clinical failure (OR: 0.16, 95% CI: 0.06–0.42, p < 0.001), while prior urinary tract infection (UTI) increased failure risk (OR: 2.87, 95% CI: 1.3–6.3). Conclusions: Ciprofloxacin was more effective than cefuroxime in treating ABP-E. coli. Patients with recent UTIs may need closer monitoring or alternative therapies.